Four Novel Caudoviricetes Bacteriophages Isolated from Baltic Sea Water Infect Colonizers of Aurelia aurita - Melissa Stante; Nancy Weiland-Bräuer; Urska Repnik; Almut Werner; Marc Bramkamp; Cynthia M. Chibani; Ruth A. Schmitz (Viruses)
The moon jellyfish Aurelia aurita is associated with a highly diverse microbiota changing with provenance, tissue, and life stage. While the crucial relevance of bacteria to host fitness is well known, bacteriophages have often been neglected. Here, we aimed to isolate virulent phages targeting bacteria that are part of the A. aurita-associated microbiota. Four phages (Pseudomonas phage BSwM KMM1, Citrobacter phages BSwM KMM2–BSwM KMM4) were isolated from the Baltic Sea water column and characterized. Phages KMM2/3/4 infected representatives of Citrobacter, Shigella, and Escherichia (Enterobacteriaceae), whereas KMM1 showed a remarkably broad host range, infecting Gram-negative Pseudomonas as well as Gram-positive Staphylococcus. All phages showed an up to 99% adsorption to host cells within 5 min, short latent periods (around 30 min), large burst sizes (mean of 128 pfu/cell), and high efficiency of plating (EOP > 0.5), demonstrating decent virulence, efficiency, and infectivity. Transmission electron microscopy and viral genome analysis revealed that all phages are novel species and belong to the class of Caudoviricetes harboring a tail and linear double-stranded DNA (formerly known as Siphovirus-like (KMM3) and Myovirus-like (KMM1/2/4) bacteriophages) with genome sizes between 50 and 138 kbp. In the future, these isolates will allow manipulation of the A. aurita-associated microbiota and provide new insights into phage impact on the multicellular host.